PENGEMBANGAN DAYA SAING UMKM DI ERA INDUSTRI 4.0 BERBASIS DIGITALISASI - syamsul arifin; Nur Farida; Nuryadi; Hadi Nasution; Agus Alhadi; Siti Nur Amanah; Ernawati (edujavare, 2024)
The KKN program is designed to provide students with direct experience in contributing to society and the surrounding environment, by integrating the knowledge and skills acquired during learning at university. The main aim of KKN is to help students understand and experience social, economic and cultural realities in society, as well as to develop social skills, leadership and communication abilities. In this way, we hope to support increasing the competitiveness of MSMEs and their contribution to the local economy in the increasingly digital Industry 4.0 era. In this context, Community Service Program (KKN) is an opportunity for students to contribute to helping MSMEs overcome these challenges and exploit the potential of digital technology. Students from various universities throughout Indonesia can participate in KKN programs in various regions, including Surabaya, with various relevant themes.